THE IMPLEMENTATION OF GENRE BASED APPROACH TO TEACHING WRITING NARRATIVE TEXTS : A Qualitative Experiment in One State Junior High School in Musi Banyuasin Regency, South Sumatera Province - Pirilani, Endang Lovita (2017)
The ability to write texts plays an important role among EFL students in Indonesia. To write English texts, students need knowledge of grammar, structures of text, vocabulary, usage of expressions, paragraphing, etc. However, students still have problems in writing. This study aims to find out how Genre Based Approach helps the students develop their skill in writing a narrative text. This study also explored the students' attitude towards the implementation of GBA. It was conducted in one state junior high school in Musi Banyuasin Regency, South Sumatera Province. The data where gathered from classroom observations, interview, questionnaire, and students written texts. The analysis indicates that first; the activities presented in the stages of GBA have helped the students develop their ability in writing a narrative text. The analysis also shows that the students' writing ability developed in term of schematic structure and language features of a narrative text. Second, regarding the students' attitude, most of the students show a positive attitude towards the activities during the implementation of GBA. Most of the students show their interest in (1) trying to understand and comprehend the expressions and vocabularies applied in a narrative text; (2) writing collaboratively as they could share knowledge of a narrative text or ask how to write a narrative text; and (3) editing or having feedback from both peers and teacher, thus the students could understand the mistakes in their writings. It is thus recommended that first; GBA can be implemented in teaching writing of narrative texts. Second, the teacher should build up the students' prior knowledge intensively by giving more models of texts and provide more feedback.;---Kemampuan menulis teks berbahasa Inggris berperan penting bagi siswa-siswa dalam konteks pendidikan di Indonesia. Untuk itu dibutuhkan kemampuan dan pengetahuan mengenai tata bahasa, struktur teks, kosakata, ungkapan-ungkapan, paragraph, dan lainnya. Pada kenyataannya, banyak siswa mengalami kesulitan dalam menulis. Studi ini bertujuan untuk menemukan bagaimana Pendekatan Berbasis Genre (GBA) membantu siswa-siswa mengembangkan kemampuan mereka dalam menulis jenis teks naratif. Studi ini juga mengeksplor sikap siswa terhadap pengimplementasian GBA dalam pengajaran Bahasa Inggris di kelas. Studi ini dilakukan di satu SMPN di Kabupaten Musi Banyuasin, Propinsi Sumatera Selatan. Temuan dari observasi kelas, interviu, kuestionair, dan teks-teks tulisan anak mengindikasikan pertama, aktifitas-aktifitas seperti yang disarankan oleh teori GBA telah membantu siswa mengembangkan kemampuan mereka dalam menulis jenis teks naratif. Hasil analisa teks-teks yang ditulis oleh siswa-siswa yang mewakili kelompok siswa bekemampuan rendah, sedang, dan tinggi menunjukkan adanya perkembangan kemampuan menulis mereka terlebih di bagian struktur teks naratif dan fitur-fitur kebahasaannya. Kedua, hampir semua siswa-siswa menunjukkan siswa positif terhadap aktifitas-aktifitas yang dilakukan selama implementasi GBA. Banyak siswa menunjukkan ketertarikan pada kegiatan-kegiatan GBA, seperti (1) mempelajari kosakata dan ungkapan yang ada dalam teks naratif; (2) menulis berkelompok, karena di dalam kelompok mereka dapat berbagi pengetahuan mengenai teks naratif dan bertanya cara menulis teks naratif; (3) meng-edit dan mendapatkan umpan-balik dari teman dan guru, sehingga siswa dapat mengerti kesalahan dalam tulisan mereka. Oleh karena itu, penelitian ini merekomendasikan pertama, GBA dapat diimplementasikan dalam pengajaran menulis teks naratif. Kedua, pengetahuan dasar siswa hendaknya dibangun secara intensif dengan cara memberi banyak model teks naratif dan umpan balik.